Phobos and Mars orbit as a base for asteroid exploration and mining. (May 2022) - Taylor, Anthony J.; McDowell, Jonathan C.; Elvis, Martin
Abstract: The number and total mass of high value near-Earth asteroids (NEOs) are limited. If space exploration and mining becomes profitable then at some point it will benefit from moving on to the far greater resources of the Main Belt Asteroids (MBAs). Most MBAs are energetically too hard to reach with present technology from low Earth orbit. An alternative is to use Mars orbit as a base from which to conduct MBA research, prospecting, and mining. We have developed PARC: Python Asteroid Rendezvous Code which uses a fast Lambert's problem solver and straightforward maneuver schemes to survey the delta-v necessary to rendezvous with any known asteroid from either Earth or Mars orbit given a specified launch date and time of flight. We used PARC to investigate whether Phobos-like orbits around Mars at altitudes of ∼9000 ​km, are more energetically favorable and useful locations from which to dispatch missions to MBAs. We find that they are. From a Phobos-like orbit, around 100, 000 known MBAs have delta-v < 4 ​km ​s −1 and some 340, 000 have delta-v < 5 ​km ​s −1, nearly a thousand times that of NEOs. Unsurprisingly, the most accessible MBAs have low inclinations ( i  ​< ​5 deg) and small semi-major axes (2.0 < a < 2.5 AU). Known MBAs are much larger than NEOs, so the total mass that is accessible is larger by ∼10, 000 times the accessible mass in NEOs. As a result, a growing economy that utilizes space resources or large scale exploration missions will likely find Mars orbit convenient. The stable platform and modest gravity afforded by Phobos would make it a natural first choice. Once Mars orbit has a profitable economy, with high value trans-shipments, the Martian surface may also become an economically valuable outpost. This value may then stimulate settlement. Highlights: We present PARC: Python Asteroid Rendezvous Code, which calculates asteroid rendezvous delta-v by solving Lambert's problem. PARC is used to find the lowest delta-v transfers to all known asteroids from 2050 to 2070. The benefits of a base for asteroid exploration and mining in Mars orbit and/or on Phobos are presented.